In-situ characterization of dynamic Acidithiobacillus ferrooxidans-pyrite interaction via QCM-D-based method: Cell adhesion and biofilm formation in responding to surface sulfur speciation - Xia, Xu; Wang, Ben-fei; Xia, Jin-lan; Zhou, Yu-hang; Nie, Zhen-yuan (Journal of environmental chemical engineering, 2024)
Microbe-sulfide mineral interactions (MSMI), often manifested as biofilm formation, are ubiquitous in natural and engineered environments. Such interactions were much dependent upon the evolution of chemical species of mineral surface and microbial extracellular polymeric substances (EPS), and in-situ characterization of which have been a demanding and crucial task. In this study, quartz crystal microbalance with dissipation (QCM-D) was used to real time characterize the adhesion of Acidithiobacillus ferrooxidans onto the pyrite surface after introducing L-cysteine (an important component of EPS). And by combining with monitoring the EPS composition in biofilm by confocal laser scanning microscopy (CLSM) and the surface sulfur species by SEM-EDS and X-ray-photoelectron spectroscopy (XPS) as well as the changes in pH, ORP, [Fe2+] and [Fe3+] in solution during A. ferrooxidans-pyrite interaction, the results show that L-cysteine can lead to the Cys-S-S2Fe complex formation on pyrite surface, and under the dosage of 0.02 to 0.1 g/L of L-cysteine, the Cys-S-S2Fe complex promoted the cell adhesion and biofilm formation of A. ferrooxidans with secretion of more EPS proteins but less EPS glycoconjugates, resulting in the promotion of sulfur biooxidation with inhibition of iron biooxidation, corresponding to no obvious formation of jarosites. The higher dosage of L-cysteine (e.g., 0.2 g/L) inhibited biofilm formation, reduced iron/sulfur oxidation. These results deepen the understanding of the roles of L-cysteine on MSMI. This study demonstrates the QCM-D-based method can be widely used for in situ characterization of MSMI, and opens an alternative pathway for revealing the micro-mechanism of MSMI correlated to the macroscopic effects. [Display omitted] •The cell adhesion and biofilm formation of A. ferrooxidans on pyrite was study real time by QCM-D.•L-cysteine modification led to the production of Cys-S-S2Fe complex on pyrite surface.•The surface Cys-S-S2Fe complex stimulated A. ferrooxidans to secret more proteins for promoting S oxidation.•L-cysteine modification significantly inhibited Jarosites formation with delaying iron oxidation.